ANALYSIS OF ENGLISH TEXTBOOK WITH TITLE “ BAHASA INGGRIS “ USED IN ELEVENTH GRADE SENIOR HIGH SCHOOL IN 2013 CURRICULUM - Risca Nur Qodaria (JOLE (Journal of Language Education), 2023)
JOLE (Journal of Language Education), Vol 7 No.1 May 2023English Education Study Program, Universitas Baturaja30ANALYSIS OF ENGLISH TEXTBOOK WITH TITLE “ BAHASAINGGRIS “ USED IN ELEVENTH GRADE SENIOR HIGHSCHOOL IN 2013 CURRICULUMRisca Nur QodariaBaturaja Universityriscanurqa11@gmail.comABSTRACTThe objectives of this study are to find out the suitability of impressionistic and in-depth analysis in thetextbook entitles "Bahasa Inggris” used for the eleventh grade of Senior High School. This research isconducted by applying descriptive qualitative. The data was collected by documenting the contentmaterials on the textbook and it was analyzed by using Cunningsworth's theory. The result showed that anEnglish textbook entitle “Bahasa Inggris" fulfilled the criteria proposed in Cunningsworth's theoryconcerning the impressionistic textbook analysis with score 73% and in-depth textbook analysis with thesummative score 86%. From those summative scores, the textbook was categorized as a fair and goodenough textbook and suitable enough to use as media in teaching and learning process